Mycotoxins in poultry feed and feed ingredients from sub-Saharan Africa and their impact on the production of broiler and layer chickens: A review - Ochieng, P.E.; Scippo, M.-L.; Kemboi, D.C.; Croubels, S.; Okoth, S.; Kang'ethe, Erastus K.; Doupovec, B.; Gathumbi, J.K.; Lindahl, Johanna F.; Antonissen, G. (MDPI, 2021)
The poultry industry in sub-Saharan Africa (SSA) is faced with feed insecurity, associated with high cost of feeds, and feed safety, associated with locally produced feeds often contaminated with mycotoxins. Mycotoxins, including aflatoxins (AFs), fumonisins (FBs), trichothecenes, and zearalenone (ZEN), are common contaminants of poultry feeds and feed ingredients from SSA. These mycotoxins cause deleterious effects on the health and productivity of chickens and can also be present in poultry food products, thereby posing a health hazard to human consumers of these products. This review summarizes studies of major mycotoxins in poultry feeds, feed ingredients, and poultry food products from SSA as well as aflatoxicosis outbreaks. Additionally reviewed are the worldwide regulation of mycotoxins in poultry feeds, the impact of major mycotoxins in the production of chickens, and the postharvest use of mycotoxin detoxifiers. In most studies, AFs are most commonly quantified, and levels above the European Union regulatory limits of 20 μg/kg are reported. Trichothecenes, FBs, ZEN, and OTA are also reported but are less frequently analyzed. Co-occurrences of mycotoxins, especially AFs and FBs, are reported in some studies. The effects of AFs on chickens’ health and productivity, carryover to their products, as well as use of mycotoxin binders are reported in few studies conducted in SSA. More research should therefore be conducted in SSA to evaluate occurrences, toxicological effects, and mitigation strategies to prevent the toxic effects of mycotoxins.